Theoretical foundations for the parameters of a potato digger for a moto-block - Rajabov Jaloladdin; Xusainov Baxtiyor; Atajanova Saodat; Norchaev Davron; Gaybullaev Burxon (BIO Web of Conferences)
The article provides an analysis of the current state and relevance of potato cultivation in the soil and climatic conditions of our republic, as well as the necessary equipment to be used. It presents analytical and theoretical information on the scientific foundations of using a motor-block and an attached potato digger for harvesting potatoes grown in household plots or small farms. Additionally, the article substantiates the parameters of the potato digger that ensure efficient potato harvesting with minimal energy consumption and explores the process of interaction with the soil. According to the results of the conducted research, the potato digger should have the following specifications: a length of 100 cm, a mounting device length of 30 cm, an elevator length of 53 cm, a share width of 39 cm and length of 33 cm, an installation angle of the share relative to the horizon of 25°, and an opening angle of the tip between 80–90°. The support wheel should have a diameter of 0.35 m and a width of 12 cm. The width of the teeth should be less than or equal to 6 cm, and their number should be 10.